Engineering Properties of Palm Kernel Shell Fiber Reinforced Concrete - Olawuni, Kayode Bamikole; Eren, Ozgur (Nordic Concrete Federat, 2014)
In this study, Palm Kernel Shell (PKS) partly replaced with conventional aggregates. The effect of PKS and steel fibers were experimented. Several concrete mixes were prepared with different PKS coarse aggregates amount of 25%, 50% and 75% that replaced by mass of 10 mm size conventional coarse aggregates. PKS fine aggregates amount of 10%, 7.5% and 5% replaced by mass of conventional fine aggregates. This procedure was imitated for target mean strength of 30MPa. The compressive strength, Schmidt hammer and splitting tensile strength of concretes was performed at the curing age of 28 days.
Keywords: aggregates; fiber; mix design; testing